Controversies in the management of anti-TNF therapy in patients with Crohn’s disease: a Delphi consensus - Ignacio Marin-Jimenez; Guillermo Bastida; Daniel Carpio; Fernando Muñoz; Yago González-Lama; Elena Ricart; Daniel Ceballos; Daniel Ginard; Luis Menchen (BMJ Open Gastroenterology)
Background Despite research, there are still controversial areas in the management of Crohn’s disease (CD).Objective To establish practical recommendations on using anti-tumour necrosis factor (TNF) drugs in patients with moderate-to-severe CD.Methods Clinical controversies in the management of CD using anti-TNF therapies were identified. A comprehensive literature review was performed, and a national survey was launched to examine current clinical practices when using anti-TNF therapies. Their results were discussed by expert gastroenterologists within a nominal group meeting, and a set of statements was proposed and tested in a Delphi process.Results Qualitative study. The survey and Delphi process were sent to 244 CD-treating physicians (response rate: 58%). A total of 14 statements were generated. All but two achieved agreement. These statements cover: (1) use of first-line non-anti-TNF biological therapy; (2) role of HLA-DQA1*05 in daily practice; (3) attitudes in primary non-response and loss of response to anti-TNF therapy due to immunogenicity; (4) use of ustekinumab or vedolizumab if a change in action mechanism is warranted; (5) anti-TNF drug level monitoring; (6) combined therapy with an immunomodulator.Conclusion This document sought to pull together the best evidence, experts’ opinions, and treating physicians’ attitudes when using anti-TNF therapies in patients with CD.